Surgical Management of Clavicle Fracture with Precontoured Locking Plate - Bipan Shrestha; Prakriti Raj Kandel; Kishor Man Shrestha; Shreshal Shrestha; Subash Pandey; Pradip Chhetri (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Traditionally, displaced midshaft clavicle fractures have been treated by nonoperative methods but had high rates of malunion and prolong pain. Therefore, ﬁxation with precontoured locking compression plates (LCP) has become the ideal mode of treatment as plate ﬁxation restores the anatomy and provides excellent radiological and functional outcomes. MATERIAL AND METHODS This prospective and observational study was carried out in Orthopedics department of Universal College of Medical Sciences-Teaching Hospital (UCMS-TH) from January 2022 to March 2024. After Ethical clearance (UCMS/IRC/164/21) from Institutional Review Committee (IRC) and informed written consent, all selected patients with midshaft clavicle fracture were treated with precontoured locking plate. Post-operatively patients were regularly followed at 6 weeks, 3 months and 6 months. At 6 months, functional outcome was assessed by Constant and Murley Score (CMS). Descriptive statistics like frequency, percentage, mean and standard deviation were used to analyze the data by SPSS 20 whereas Chi square test was used as an inferential statistics. RESULTS In our study of 50 cases, the mean age group was 35±7.2 years (20-46 years). Most of the cases were Robinson 2A2 (60%) type. The average duration of fracture union was 4.14± 0.7 months (3-6 months). Only 1 patient (2%) had superﬁcial wound infection and another 1 patient (2%) had implant failure. The average CMS and Visual Analogue Scale (VAS) at 6 months was 96.26±2.57 (86-99) and 0.06±0.23 (0-1) respectively. At 6 months, 96% cases had excellent result. Finally, we observed statistically signiﬁcant difference between the fracture classiﬁcation and fracture union time (p=0.003); as well as fracture classiﬁcation and patient satisfaction (p=0.004). CONCLUSION Precontoured locking plate is an effective treatment method for midshaft clavicle fracture in adults with beneﬁts of early pain relief, early union and excellent functional outcome.